2020
DOI: 10.1177/0093854820913585
|View full text |Cite
|
Sign up to set email alerts
|

Belief in Redeemability and Punitive Public Opinion: “Once a Criminal, Always a Criminal” Revisited

Abstract: In 2009, Maruna and King presented results from a British survey showing that the public’s belief in the redeemability of people who committed offenses curbed their level of punitiveness. Based on a 2017 national survey in the United States ( n = 1,000), the current study confirms that redeemability is negatively related to punitive attitudes. In addition, the analyses reveal that this belief predicts support for rehabilitation and specific inclusionary policies (i.e., ban-the-box in employment, expungement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 63 publications
4
68
0
Order By: Relevance
“…Consistent with the entity-incremental perspective in social psychology (Plaks et al, 2009) and the growing literature within criminology (see, e.g., Burton et al, 2020;Maruna & King, 2009), the current analysis showed that belief in redeemability is a robust predictor across different measures of support for criminal record expungement. In other words, the tyranny of just deserts, wherein expressive concerns drive general punitiveness (Darley, 2009), appears to end after sentencing, with utilitarian concerns about desistance and dangerousness taking on increased importance (Lehmann et al, 2020).…”
Section: Criminological Implicationssupporting
confidence: 83%
See 4 more Smart Citations
“…Consistent with the entity-incremental perspective in social psychology (Plaks et al, 2009) and the growing literature within criminology (see, e.g., Burton et al, 2020;Maruna & King, 2009), the current analysis showed that belief in redeemability is a robust predictor across different measures of support for criminal record expungement. In other words, the tyranny of just deserts, wherein expressive concerns drive general punitiveness (Darley, 2009), appears to end after sentencing, with utilitarian concerns about desistance and dangerousness taking on increased importance (Lehmann et al, 2020).…”
Section: Criminological Implicationssupporting
confidence: 83%
“…Some support also was manifested for community standing-whether a former offender volunteered in the community and would be recommended for expungement by neighbors. Signaling does not depend on an existing belief in offender redeemability, which our data show is related to support for record closure (see also Burton et al, 2020). Rather, it is a means of persuading others that a person's redeemability is a proven fact or evidence based.…”
Section: Policy Implicationsmentioning
confidence: 48%
See 3 more Smart Citations